Strategi Bauran Pemasaran Dalam Pengembangan Usaha Dengan Metode PLC (Product Life Cycle) - Lisa Sulistyawati; Hasna Wijanarko (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Business is an activity carried out to earn profits and fulfill daily needs, both activities carried out daily or activities in the business sector or buying and selling activities of a product. Clothing is included in one of the primary needs, a designation commonly known as clothing needs which are also important for humans. In addition, this makes clothes mainly clothes to be one of the types of fashion that has the fastest development because many people need clothes more than other types of fashion such as bags, shoes or others. Thriftshop “Projectnine” at Simo Sidomulyo Baru No. 29 A Surabaya is one example of the many thriftshop businesses that are currently booming, because they are considered easy to run, have a low risk of failure and the initial capital is not too large. The large number of similar competitors that exist makes business development important for Thriftshop